MANAGEABILITY AND SPONTANEITY AS PROBLEMS OF DEVELOPMENT OF DEMOCRACY IN CONDITIONS OF INFORMATION SOCIETY - Комарова, Т. Г.; Тихонова, Л. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
Problems of electoral and liberal democracy and political management in conditions ofinformatization and globalization of modern society are considered in this article. Authors analyzechallenges to democratic method of society management that exists in the information epoch. Theyinvestigate how manageability and spontaneity in politics at the present stage are correlated, in whatnew factors of development they are expressed.